PSYCHOMETRIC PROPERTIES OF THE ATHLETE BURNOUT QUESTIONNAIRE FOR YOUNG BRAZILIAN ATHLETES - Dartagnan Pinto Guedes; Rafael Octaviano de Souza (Journal of Physical Education)
ABSTRACT The objective of this study was to identify the psychometric properties of the Athlete Burnout Questionnaire (ABQ) for young Brazilian athletes. The questionnaire was administered to a sample of 1,217 young athletes (410 girls and 807 boys) aged 12 to 17 years. Exploratory factor analysis, followed by confirmatory factor analysis, was performed to identify the initial psychometric properties. Cronbach's alpha coefficient was used to assess the internal consistency of each factor of the ABQ associated with burnout. The results confirmed the structure of the three originally proposed factors (physical/emotional exhaustion, reduced sense of personal accomplishment, and sport devaluation) based on the following statistical measures: χ2/d.f. = 2.89, CFI = 0.930, GFI = 0.928, AGFI = 0.937, and RMSR = 0.068 [CI90%: 0.065 - 0.072]. Cronbach's alpha ranged from 0.80 to 0.87. In conclusion, the psychometric qualities of the ABQ were satisfactory for young Brazilian athletes, thus permitting the application of the questionnaire in future studies in Brazil.